Cognitive phenotypes in frontal lobe epilepsy. Issue 7 (3rd May 2022) - Arrotta, Kayela; Reyes, Anny; Kaestner, Erik; McDonald, Carrie R.; Hermann, Bruce P.; Barr, William B.; Sarmey, Nehaw; Sundar, Swetha; Kondylis, Efstathios; Najm, Imad; Bingaman, William; Busch, Robyn M.
Abstract: Objective: Neuropsychological profiles are heterogeneous both across and within epilepsy syndromes, but especially in frontal lobe epilepsy (FLE), which has complex semiology and epileptogenicity. This study aimed to characterize the cognitive heterogeneity within FLE by identifying cognitive phenotypes and determining their demographic and clinical characteristics. Method: One hundred and six patients (age 16–66; 44% female) with FLE completed comprehensive neuropsychological testing, including measures within five cognitive domains: language, attention, executive function, processing speed, and verbal/visual learning. Patients were categorized into one of four phenotypes based on the number of impaired domains. Patterns of domain impairment and clinical and demographic characteristics were examined across phenotypes. Results: Twenty‐five percent of patients met criteria for the Generalized Phenotype (impairment in at least four domains), 20% met criteria for the Tri ‐ Domain Phenotype (impairment in three domains), 36% met criteria for the Domain ‐ Specific Phenotype (impairment in one or two domains), and 19% met criteria for the Intact Phenotype (no impairment). Language was the most common domain‐specific impairment, followed by attention, executive function, and processing speed. In contrast, learning was the least impacted cognitive domain. The Generalized Phenotype had fewer years of education compared to the Intact Phenotype, but otherwise, there was no differentiation between phenotypes in demographic and clinical variables. However, qualitative analysis suggested that the Generalized and Tri ‐ Domain Phenotypes had a more widespread area of epileptogenicity, whereas the Intact Phenotype most frequently had seizures limited to the lateral frontal region. Significance: This study identified four cognitive phenotypes in FLE that were largely indistinguishable in clinical and demographic features, aside from education and extent of epileptogenic zone. These findings enhance our appreciation of the cognitive heterogeneity within FLE and provide additional support for the development and use of cognitive taxonomies in epilepsy.